2020
DOI: 10.1111/jpn.13458
|View full text |Cite
|
Sign up to set email alerts
|

The effects of eggshell calcium (Biomin H®) and its combinations with alfacalcidol (1α‐hydroxyvitamin D3) and menaquinone‐7 (vitamin K2) on ovariectomy‐induced bone loss in a rat model of osteoporosis

Abstract: The purpose of this study was to investigate the impact of eggshell calcium (Biomin H® dietary supplement) and its combinations with alfacalcidol (1α‐hydroxyvitamin D3) and menaquinone‐7 (vitamin K2) on ovariectomy‐induced bone loss in rats. Adult female rats (n = 48) were divided into 6 groups of 8 individuals each: sham‐operated rats (SHAM); ovariectomized (OVX) rats untreated; OVX rats treated with Biomin H® (BIO); OVX rats simultaneously receiving Biomin H®, vitamin D3 (BIO + D3); OVX rats simultaneously t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Examined parameters of the trabecular bone (BV/TV, Tb.N., Tb.Th., BMD, and BS) are shown in Table 2 . High resolution scans with 14.8 µm voxel size were obtained in both ROIs, including scanning parameters 70 kVp, 200 mA, 300 ms, and 0.5 mm aluminium filter [ 44 ]. Thin sections from cortical bone tissue (2D imaging) were prepared according to Martiniakova et al [ 45 ] and were evaluated by established classification systems [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Examined parameters of the trabecular bone (BV/TV, Tb.N., Tb.Th., BMD, and BS) are shown in Table 2 . High resolution scans with 14.8 µm voxel size were obtained in both ROIs, including scanning parameters 70 kVp, 200 mA, 300 ms, and 0.5 mm aluminium filter [ 44 ]. Thin sections from cortical bone tissue (2D imaging) were prepared according to Martiniakova et al [ 45 ] and were evaluated by established classification systems [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Microcomputed tomography (microCT, μCT 50, Scanco Medical, Brüttisellen, Switzerland) was used to designate selected quantitative 3D parameters of cortical bone (relative bone volume, relative bone volume with marrow cavity, BMD, cortical bone thickness and bone surface) and trabecular bone sections (relative bone volume, trabecular number, trabecular thickness, BMD and bone surface). The measurement parameters and scanning regions of interest were the same as those in the study by Omelka et al [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar results have been obtained in the study of Brennan et al [ 128 ] using calcium-rich marine multimineral complex which significantly preserved trabecular bone microarchitecture and slowed the onset of bone loss in comparison with calcium carbonate. Omelka et al [ 129 ] demonstrated the beneficial effects of co-administration of egg shell Ca with vitamins D3 and K2, as well as egg shell Ca with vitamin D3 only on the inhibition of bone loss in ovariectomized (OVX) rats. These two combinations significantly improved both biochemical and densitometric parameters consistent with osteoporosis.…”
Section: Micronutrients and Osteoporosismentioning
confidence: 99%
“…Therefore, vitamin D supplementation, alone or in combination with Ca, appeared to be essential to enhance the positive effects of any specific therapy in such patients. In this context, simultaneous vitamin D and Ca intake in the treatment of osteoporosis is more effective than individual administrations [ 129 , 172 , 173 ].…”
Section: Micronutrients and Osteoporosismentioning
confidence: 99%